2017
DOI: 10.1152/japplphysiol.00117.2017
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of exercise training in heart failure are lost in male diabetic rats

Abstract: Exercise training has been demonstrated to have beneficial effects in patients with heart failure (HF) or diabetes. However, it is unknown whether diabetic patients with HF will benefit from exercise training. Male Wistar rats were fed either a standard (Sham, n = 53) or high-fat, high-sucrose diet ( n = 66) for 6 mo. After 2 mo of diet, the rats were already diabetic. Rats were then randomly subjected to either myocardial infarction by coronary artery ligation (MI) or sham operation. Two months later, heart f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
1
0
1
Order By: Relevance
“…Analysis results showed that in the random model, the SMD was − 1.260 (CI 95%, − 8.630 to 6.110; p = 0.738; Fig. 7 A) [ 41 , 42 ]. Two experiments (n = 56; 16 Exc + DM and 16 DM) released data on IL-1β in DM and Exc.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis results showed that in the random model, the SMD was − 1.260 (CI 95%, − 8.630 to 6.110; p = 0.738; Fig. 7 A) [ 41 , 42 ]. Two experiments (n = 56; 16 Exc + DM and 16 DM) released data on IL-1β in DM and Exc.…”
Section: Resultsmentioning
confidence: 99%
“…Não é novidade que o TFA tem se mostrado uma ferramenta de prevenção amplamente utilizada para o controle de peso corporal, da adiposidade e da obesidade (BIRD et al, 2017;BOUDIA et al, 2017). Nossos resultados mostraram que o TFA foi eficaz para o controle de peso corporal dos animais treinados comparado aos sedentários, independente da dieta.…”
Section: Discussionunclassified